Mosloflavone-Resveratrol Hybrid TMS-HDMF-5z Exhibits Potent In Vitro and In Vivo Anti-Inflammatory Effects Through NF-κB, AP-1, and JAK/STAT Inactivation - Kim, Seo-Yeon; Hassan, Ahmed H.E.; Chung, Kyung-Sook; Kim, Su-Yeon; Han, Hee-Soo; Lee, Hwi-Ho; Jung, Seang-Hwan; Lee, Kwang-Young; Shin, Ji-Sun; Jang, Eungyeong; Yoon, Seolmin; Lee, Yong Sup; et al. (Frontiers in Pharmacology, 2022)
TMS-HDMF-5z is a hybrid of the natural products mosloflavone and resveratrol. It was discovered to show potent inhibitory effects against lipopolysaccharide (LPS)-induced production of inflammatory mediators in RAW 264.7 macrophages. However, its mechanism of action is unknown. Hence this study aimed to demonstrate and explore in vitro and in vivo anti-inflammatory effects of TMS-HDMF-5z and its mechanism of action employing RAW 264.7 macrophages and carrageenan-induced hind paw edema. This work revealed that TMS-HDMF-5z suppressed the LPS-induced inducible nitric-oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) at the protein, mRNA, and promoter binding levels and tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6, and interferon-β (IFN-β) at the mRNA expression in RAW 264.7 macrophages. The results showed that TMS-HDMF-5z reduced the transcription and DNA binding activities of nuclear factor-κB (NF-κB) through inhibiting nuclear translocation of p65 and phosphorylation of κB inhibitor α (IκBα), IκB kinase (IKK), and TGF-β activated kinase 1 (TAK1). Additionally, TMS-HDMF-5z attenuated the LPS-induced transcriptional and DNA binding activities of activator protein-1 (AP-1) by suppressing nuclear translocation of phosphorylated c-Fos, c-Jun, and activating transcription factor 2 (ATF2). TMS-HDMF-5z also reduced the LPS-induced phosphorylation of Janus kinase 1/2 (JAK1/2), signal transducers and activators of transcription 1/3 (STAT1/3), p38 mitogen-activated protein kinase (MAPK), and MAPK-activated protein kinase 2 (MK2). In rats, TMS-HDMF-5z alleviated carrageenan-induced hind paw edema through the suppressing iNOS and COX-2 via NF-κB, AP-1, and STAT1/3 inactivation. Collectively, the TMS-HDMF-5z-mediated inhibition of NF-κB, AP-1, and STAT1/3 offer an opportunity for the development of a potential treatment for inflammatory diseases.